STUDY ON FIBER OF THE MENGKUANG PANDANUS (PANDANUS ARTOCAPUS) LEAVES FOR NATURAL FISHING GEAR MATERIAL - Fika Yulia Rachmah; Nofrizal '; Irwandy Syofyan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
A series histological observation on the fiber structure of mengkuang pandanus (Pandanus artocapus) leaves and breaking strength test were conducted for identifying potential of mengkuang pandanus leaves as natural fiber for making a rope as fishing gear material. The result show that the mengkuang pandanus leaves had epidermis and parenchyma highly density, as a result the structure fiber of pandan mengkuang leaves reach 4 kgf. The elongation of mengkuang pandanus leaves fiber was 20.1 mm and water absorption ability and sinking speed were 1 % and  0,59 cm/second respectively. Structure, breaking strength, water absorption ability and sinking speed of the mengkuang pandanus leaves are discussed on this paper detail. Keyword : breaking strength, histological observation, elongation, mengkuang pandanus (Pandanus artocapus), sinking speed, water absorption ability